2013
DOI: 10.2105/ajph.2012.301110
|View full text |Cite
|
Sign up to set email alerts
|

Health Disparities Among Lesbian, Gay, and Bisexual Older Adults: Results From a Population-Based Study

Abstract: Objectives We investigated health disparities among lesbian, gay, and bisexual (LGB) adults aged 50 years and older. Methods We analyzed data from the 2003–2010 Washington State Behavioral Risk Factor Surveillance System (n = 96 992) on health outcomes, chronic conditions, access to care, behaviors, and screening by gender and sexual orientation with adjusted logistic regressions. Results LGB older adults had higher risk of disability, poor mental health, smoking, and excessive drinking than did heterosexu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
575
4
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 785 publications
(620 citation statements)
references
References 47 publications
30
575
4
11
Order By: Relevance
“…Our expectation that prior military and identity stigma would be positively related to depressive symptomatology and negatively related to psychological HRQOL was partially supported. Identity stigma was positively associated with depressive symptomatology and negatively with psychological HRQOL, congruent with previous findings on these relationships among transgender older adults (Fredriksen-Goldsen et al, 2013, 2015. Unexpectedly, we found that prior military service was associated with lower depressive symptomatology and greater psychological HRQOL, in contrast to much previous research that has typically cast military service primarily in terms of negative outcomes.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Our expectation that prior military and identity stigma would be positively related to depressive symptomatology and negatively related to psychological HRQOL was partially supported. Identity stigma was positively associated with depressive symptomatology and negatively with psychological HRQOL, congruent with previous findings on these relationships among transgender older adults (Fredriksen-Goldsen et al, 2013, 2015. Unexpectedly, we found that prior military service was associated with lower depressive symptomatology and greater psychological HRQOL, in contrast to much previous research that has typically cast military service primarily in terms of negative outcomes.…”
Section: Discussionsupporting
confidence: 88%
“…Identity stigma, the internalization of prevailing societal attitudes and beliefs relative to dominant and stigmatized groups, is a major stressor associated with depression among transgender older adults (Fredriksen-Goldsen et al, 2013). Identity stigma has been characterized as insidious trauma (Szymanski & Balsam, 2011).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…The health risks and health behaviours of LB women are thought to negatively impact their gynaecological health. These include increased tobacco and alcohol use,2, 3 higher body mass index (BMI),4, 5, 6 and reduced uptake of cervical cytology screening 7, 8, 9. Lesbians are also said to have fewer reproductive behaviours that are associated with protection from various reproductive system cancers than heterosexual women, including use of oral contraceptives, childbirth and breastfeeding 10, 11.…”
Section: Introductionmentioning
confidence: 99%